Transgenic Manipulation of the Metabolism of Polyamines in Poplar Cells - Bhatnagar, Pratiksha (American Society of Plant Physiologists, 2001)
The metabolism of polyamines (putrescine, spermidine, and spermine) has become the target of genetic manipulation because of their significance in plant development and possibly stress tolerance. We studied the polyamine metabolism in non-transgenic (NT) and transgenic cells of poplar (Populus nigra × maximowiczii) expressing a mouse Orn decarboxylase (odc) cDNA. The transgenic cells showed elevated levels of mouse ODC enzyme activity, severalfold higher amounts of putrescine, a small increase in spermidine, and a small reduction in spermine as compared with NT cells. The conversion of labeled ornithine (Orn) into putrescine was significantly higher in the transgenic than the NT cells. Whereas exogenously supplied Orn caused an increase in cellular putrescine in both cell lines, arginine at high concentrations was inhibitory to putrescine accumulation. The addition of urea and glutamine had no effect on polyamines in either of the cell lines. Inhibition of glutamine synthetase by methionine sulfoximine led to a substantial reduction in putrescine and spermidine in both cell lines. The results show that: (a) Transgenic expression of a heterologous odc gene can be used to modulate putrescine metabolism in plant cells, (b) accumulation of putrescine in high amounts does not affect the native arginine decarboxylase activity, (c) Orn biosynthesis occurs primarily from glutamine/glutamate and not from catabolic breakdown of arginine, (d) Orn biosynthesis may become a limiting factor for putrescine production in the odc transgenic cells, and (e) assimilation of nitrogen into glutamine keeps pace with an increased demand for its use for putrescine production.